KEMAMPUAN MEMAHAMI UNSUR INTRINSIK CERITA PENDEK SISWA KELAS XI SMA NEGERI 1 KUANTAN HILIR SEBERANG KABUPATEN KKUANTAN SINGINGI - Depi Lestari; Nursal Hakim; Abdul Razak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to understand the intrinsic elements of a short story student of class XI SMA Negeri 1 Kuantan Hilir Seberang Kabupaten Kuantan Singingi. This research is using descriptive metods. The populations in this research is all student class XI SMA Negeri 1 Kuantan Hilir Seberang Kabupaten Kuantan Singingi. The sample in this research are 60 student. The technique collecting data is a tes reading a matter of mat with 4 option/alternative. The research concluded that the intrinsic elements of a short story student of class XI SMA Negeri 1 Kuantan Hilir Seberang Kabupaten Kuantan Singingi category low with an average value of 66,66.Keywords: the capacity to understand, the intrinsic elementsof a short story